Frequency and Clinical Manifestations of Caesarean Section Scar Defects - Ome Kulsoom; Habiba Sharaf Ali; Ayesha Zulfiqar; Saadia Sarwar (ziauddin University, 2020)
Background: Caesarean Sections (CS), significantly on the rise worldwide, have been found frequently complicated with the presence of a scar at the site of CS. It is associated with various gynecological problems like postmenstrual spotting, infertility, miscarriage, and uterine rupture. The objective of this study was to determine the frequency of CS scar defects and associated gynaecological symptoms. Methods: This cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, Ziauddin University Hospital Karachi from October 1st, 2017 to March 1st, 2018. A total of 162 patients' (aged 20-40 years) were included, with CS history (elective or emergency) and complaints of chronic pelvic pain, infertility or menstrual irregularities, after an informed consent. Demographic details and medical history were recorded on performa. Chi-square was used to establish association between categorical variable such presence of scar defect, clinical symptoms and the shape of the defect. Results: Out of 162 patients, 86(53.1%) had one and 76(46.9%) had more than one caesarean scar. Majority of the patients 97(59.9%) were found to have scar defect (NICHE) present while in 65 (40.1%) patients had no caesarean scar defect. Regarding menstrual cycle, 58(35.8%) had heavy bleeding, 39(24.1%) continuous bleeding, and 27 (16%) irregular cycle. Significant association (p<0.05) was found between menstrual irregularity, pelvic pain, infertility and scar defects. Different shapes of scar (niche) were noted triangular 46(28.4%) droplet 26(16%), oval and others such as rectangular and inclusion cyst on ultrasonographic . Conclusion: Multiple Caesarean sections are predisposing factors for Caesarean scar defects. Menstrual irregularity, pelvic pain, infertility and scar defects were found significantly associated with Caesarean sections (p<0.05).